2008
DOI: 10.1177/0363546508326715
|View full text |Cite
|
Sign up to set email alerts
|

Varus Alignment Leads to Increased Forces in the Anterior Cruciate Ligament

Abstract: A varus alignment in an anterior cruciate ligament-deficient knee does not necessarily lead to a varus thrust and therefore does not always need operative varus alignment correction. However, in an unstable anterior cruciate ligament-deficient knee with a varus thrust, it might be safer to perform a high valgus tibial osteotomy to minimize the risk of an anterior cruciate ligament reconstruction failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(78 citation statements)
references
References 26 publications
1
69
0
1
Order By: Relevance
“…Indeed, morphological knee parameters such as tibial slope, notch width, and femoral condyle shape have been correlated with increased risk of ACL injury, ACL reconstruction failure or post-operative laxity (17). Furthermore, with regard to knee alignment, varus deformity has been demonstrated to increase tension on the ACL (18). Compliance with the rehabilitation protocol Obviously, in order to allow a safe return to sport and J oints maximise the patient's outcome an appropriate rehabilitation protocol is crucial.…”
Section: Anatomical Featuresmentioning
confidence: 99%
“…Indeed, morphological knee parameters such as tibial slope, notch width, and femoral condyle shape have been correlated with increased risk of ACL injury, ACL reconstruction failure or post-operative laxity (17). Furthermore, with regard to knee alignment, varus deformity has been demonstrated to increase tension on the ACL (18). Compliance with the rehabilitation protocol Obviously, in order to allow a safe return to sport and J oints maximise the patient's outcome an appropriate rehabilitation protocol is crucial.…”
Section: Anatomical Featuresmentioning
confidence: 99%
“…Increasing degrees of varus alignment up to the WBL at 100% does not appear to compromise the results of ACL reconstruction in primary varus knees. van de Pol et al [26] conducted a cadaveric study in which the strain in the ACL and the lateral joint opening was measured under axial compressive limb loads with three different WBLs. The mechanical axis was set to pass the center of the knee (WBL at 0%), halfway between the medial tibial plateau (WBL at 50%), and WBL at 100%.…”
Section: Discussionmentioning
confidence: 99%
“…The decision regarding whether to recommend HTO is clinically important, because the surgery adds risk, rehabilitation would be delayed to permit union of the osteotomized site, and longterm benefits are unknown. One cadaveric study showed that varus alignment in an ACL-deficient knee does not necessarily lead to varus thrust and the authors concluded such knees do not always need HTO [26].…”
Section: Introductionmentioning
confidence: 99%
“…15,19,20 Therefore, alignment should be corrected either before or concurrently with ligament reconstruction. 19,20 We believe the same principle can be extrapolated for patients with valgus malalignment and MCL deficiency.…”
Section: Varus-producing Osteotomymentioning
confidence: 99%
“…6 For this reason, many surgeons now choose to perform a DFO to correct the valgus deformity at the knee not only in the setting of isolated lateral compartment pathology but also in the setting of medial ligamentous incompetence. 5,6,15 Although several techniques have been described, our preferred technique for unloading the lateral compartment, as well as for managing valgus malalignment in the setting of medial ligamentous incompetence, is a varus-producing lateral opening-wedge DFO. The purpose of this technical note is to describe our DFO technique using plate internal fixation with adjunctive bone allograft.…”
mentioning
confidence: 99%